2016
DOI: 10.1186/s40852-016-0049-5
|View full text |Cite|
|
Sign up to set email alerts
|

An open letter to Mr. Secretary general of the united nations to propose setting up global standards for conquering growth limits of capitalism

Abstract: We propose an international economic agenda to overcome the growth limits of capitalism that can be supported by the United Nations. Sustainable Environment based global goals should be added to sustainable economy. For this, we propose dynamic balance between three sub-economies such as open innovation, closed innovation, and social innovation sub-economy. For this, we propose to set up a UN community and a long range plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Finally, the industrial ecosystem of sharing economy is also an innovation system, so open innovation dynamics is the future research focus. At present, many scholars have made a lot of fruitful achievements in this field [55][56][57][58][59][60], which provide a solid foundation for the follow-up study of this paper.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…Finally, the industrial ecosystem of sharing economy is also an innovation system, so open innovation dynamics is the future research focus. At present, many scholars have made a lot of fruitful achievements in this field [55][56][57][58][59][60], which provide a solid foundation for the follow-up study of this paper.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…This research has shown that human-based policy dynamics and sustainable human happiness can be realized by stimulating national policies for consumer happiness in the human-needs-based sector, e.g., the healthcare industry. In this study, the innovation capability and its role in enhancing the relationship between total quality management practices and innovation performance, and the complex adaptive systems approach were used as the open innovation perspective [18,19].…”
Section: The Special Issuementioning
confidence: 99%
“…That is, if the proposed technology is applied to the production scheduling system of a real manufacturing business, then it can be expected that the quantity and quality of the product will be enhanced since the production scheduling influences them. This study uses open innovation perspectives such as (a) the innovation capability and its role in enhancing the relationship between TQM practices and innovation performance; (b) the Schumpeterian Dynamics of open innovation, and the dynamics from open innovation to evolutionary change [15,16,18].…”
Section: The Special Issuementioning
confidence: 99%
See 2 more Smart Citations